PERAN GURU PENDIDIKAN JASMANI DALAM MENGEMBANGKAN KEMAMPUAN BELAJAR GERAK ANAK: STUDI LITERATUR - Alandhani, Dafhi; Manalu, Claudia Laora; Atthariq , Raffi; Ramadhandy, Denis; Karo karo, Abta Peranata; Amansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Physical education has an important role in supporting children's motor development and movement learning abilities. Physical education teachers are the main factor in the learning process because they act as facilitators, motivators, and evaluators in the development of students' movement skills. This study aims to examine the role of physical education teachers in developing children's movement learning abilities through literature study methods. The method used is literature review by collecting various relevant scientific articles and journals regarding physical education and children's motor development. The results of the study show that the use of appropriate learning strategies such as movement demonstrations, educational games, and cooperative learning is able to improve students' motor skills and movement skills. Thus, the professional competence of physical education teachers is indispensable to create effective and enjoyable learning. Keywords: Physical education teacher, movement learning, motor development, physical education, literature study